The effectiveness of an educational program based on self-adaptation in learning basic skills in basketball for students of the Faculty of Physical Education and Sports Sciences - Hilla University - Alwan, Asst. Prof. Dr. Ali Yassin; Shubbar, Asst. Prof. Dr. Ahmed Hadi (Sulaimani Journal for Humanities, 2026)
The main objective of the learning process is to try to bring students to integration in sports performance and achieve results using the best scientific methods and means available in all sports, including basketball, which is one of the sports that are widely spread in various countries of the world, so coaches and specialists in this game began to search for the best educational methods and methods that depend on the quality of mental and intellectual abilities that the game needs, on which the required duties must be built. Therefore, the research aimed to: 1- Measuring the impact of the educational program based on self-adaptation in improving the level of skill performance of students of the Faculty of Physical Education and Sports Sciences - Hilla University 2- Analysis of the differences between the experimental group and the control group in learning basic skills in the game of basketball for students of the Faculty of Physical Education and Sports Sciences - Hilla University. 3- Identify the effect of self-adaptation on students' ability to critically evaluate self-evaluation and compare it with approved mathematical standards. 4- Recognize the level of independence and motivation that the self-adaptation tutorial has contributed to the development of their basketball skills. 5- Identify the relationship between self-adaptation and self-motivation for students of the Faculty of Physical Education and Sports Sciences - Hilla University. The study was conducted on a sample of students of the Faculty of Physical Education and Sports Sciences - Hilla University for the academic year 2023-2024, numbering (68) students distributed over four study divisions, from the research community of (168) students who were deliberately selected from the research community and were divided into two experimental and control groups, each group was represented for one of the methods, by (34) students per group and by (45%) The researchers then applied the educational program, extracted the statistical features and achieved the research objectives of the current study.
Keywords: tutorial; self adaptation